KEBIJAKAN PENDIDIKAN PANCASILA PADA PERGURUAN TINGGI GUNA MEMBANGUN KESADARAN BELA NEGARA BAGI GENERASI MUDA - oktarina, soraya (Universitas Pendidikan Muhammadiyah Sorong, 2024)
Pancasila, is the basis and ideology used by the Indonesian nation. Pancasila is also the highest guideline and legal basis for administering the life system of the Indonesian nation. Pancasila is actually the main basic capital in creating concern for the country. By continuing to practice Pancasila and upholding Pancasila, the administration of state life in Indonesia can run as it should, so that national resilience can be realized. National resilience is the ability of a country to maintain its existence, protect and defend the condition of the nation with the spirit of defending the country from its people. Upholding Pancasila can be a symbol of true national defense. Including Pancasila as a course in universities is a concrete step towards instilling the values of nationalism and defending the country. In writing, this research was studied using a descriptive qualitative approach, which was processed through literature study from various existing sources. The results of this research show that Pancasila can guide and explain to the younger generation the importance of instilling awareness of national defense in all citizens, especially the millennial generation because they are the successors and heirs to the continuity of national and state life. Education about Pancasila is important in defending the country because it helps the younger generation understand the history, principles and commitment to protecting the country's sovereignty. The packaging in providing Pancasila education and defending the country aims to enable the younger generation to understand more deeply about defending the country and the importance of a sense of nationalism to strengthen state sovereignty.